2006
DOI: 10.1111/j.1471-4159.2006.04209.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization and biological activity of the steroidogenic enzyme cytochrome P450 17α‐hydroxylase/C17, 20‐lyase (P450C17) in the frog brain and pituitary

Abstract: It is now clearly established that the brain has the capability of synthesizing various biologically active steroids including 17-hydroxypregnenolone (17OH-D 5 P), 17-hydroxyprogesterone (17OH-P), dehydroepiandrosterone (DHEA) and androstenedione (D 4 In the 1980s, Baulieu, Robel and co-workers discovered that the concentrations of pregnenolone (D 5 P), dehydroepiandrosterone (DHEA) and their sulfate esters pregnenolone-sulfate (D 5 PS) and dehydroepiandrosterone-sulfate (DHEAS) in the CNS remain elevated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 90 publications
(212 reference statements)
4
47
1
Order By: Relevance
“…Recent studies have revealed the existence of key enzymes in various mammalian and nonmammalian species such as P450scc (Tsutsui and Yamazaki 1995;London et al 2006), 3b-hydroxysteroid dehydrogenase (3b-HSD) (Sakamoto et al 2001), P450c17 (cytochrome P450 17a-hydroxylase/c17,20-lyase; Corpechot et al 1981;Do Rego et al 2007), 17b-hydroxysteroid dehydrogenase (17b-HSD) (Pelletier et al 1995;Zhou et al 2005), 5a-reductase (Saitoh et al 1982;Andersson et al 1991), P450 aromatase (Naftolin et al 1972(Naftolin et al , 1975Matsuoka et al 2006), sulfotransferase and sulfatase (Knapstein et al 1968;Strott 1996), 11b-HSD (Grosser and Axelrod 1968;Moisan et al 1990Moisan et al , 1992, and cytochrome P45011b (Ozaki et al 1991;Erdmann et al 1996). Callard et al (1978) published the first paper describing high aromatase and 5a-reductase activities, thus bringing teleost fish in the area of neurosteroid research.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed the existence of key enzymes in various mammalian and nonmammalian species such as P450scc (Tsutsui and Yamazaki 1995;London et al 2006), 3b-hydroxysteroid dehydrogenase (3b-HSD) (Sakamoto et al 2001), P450c17 (cytochrome P450 17a-hydroxylase/c17,20-lyase; Corpechot et al 1981;Do Rego et al 2007), 17b-hydroxysteroid dehydrogenase (17b-HSD) (Pelletier et al 1995;Zhou et al 2005), 5a-reductase (Saitoh et al 1982;Andersson et al 1991), P450 aromatase (Naftolin et al 1972(Naftolin et al , 1975Matsuoka et al 2006), sulfotransferase and sulfatase (Knapstein et al 1968;Strott 1996), 11b-HSD (Grosser and Axelrod 1968;Moisan et al 1990Moisan et al , 1992, and cytochrome P45011b (Ozaki et al 1991;Erdmann et al 1996). Callard et al (1978) published the first paper describing high aromatase and 5a-reductase activities, thus bringing teleost fish in the area of neurosteroid research.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies conducted over the past two decades have demonstrated that the central and peripheral nervous systems have the capacity of synthesizing steroids, the so-called ‘neurosteroids' [for reviews, see [1,2,3,4,5,6,7,8,9]. De novo formation of neurosteroids in the brain was originally demonstrated in mammals [10,11,12,13,14,15,16,17,18], and subsequently in birds [2,6,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35], amphibians [36,37,38,39,40,41,42,43,44,45,46,47] and fish [48,49,50,51]. Therefore, de novo synthesis of neurosteroids from cholesterol in the brain appears to be conserved across the subphylum vertebrata [1,2,3,4,5,6,7,8,9].…”
mentioning
confidence: 99%
“…3-HSD and CYP17-ir have been reported in different parts of the brain, including the preoptic area and the hypothalamus. P450 C17 -ir cells are widely distributed in the telencephalon, diencephalon, mesencephalon and metencephalon (Do Rego et al, 2007;Do Rego et al, 2009b).…”
Section: Results and Discussion Distribution Of P450 Aro Immunoreactimentioning
confidence: 99%